Tingkat Kesehatan Bank Sebelum dan Sesudah Implementasi PSAK 71 - Winwin Yadiati; Lolita Putri; Mochammad Ridwan (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
This study aims to assess the differences in the level of bank soundness before and after the implementation of PSAK 71 in commercial banks in Indonesia. The soundness level of 41 selected bank samples will be compared between the periods preceding and following the implementation of PSAK 71. The bank's soundness level will be evaluated using a Risk-Based Bank Rating (RBBR) based on assessment factors, including Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital. Descriptive statistics, normality tests, homogeneity tests, and the Wilcoxon test will be employed to examine whether there are any significant differences in the level of bank soundness after the implementation of PSAK 71. The results indicate that the differences are not substantial, with a decrease in risk profile, a decrease in earnings, and an increase in capital. No significant difference is found in the GCG factor.